2011
DOI: 10.3109/17435390.2010.541293
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical nanoparticles modulate specific CD4+T cell stimulation by inhibition of antigen processing in dendritic cells

Abstract: Understanding how nanoparticles may affect immune responses is an essential prerequisite to developing novel clinical applications. To investigate nanoparticle-dependent outcomes on immune responses, dendritic cells (DCs) were treated with model biomedical poly(vinylalcohol)-coated super-paramagnetic iron oxide nanoparticles (PVA-SPIONs). PVA-SPIONs uptake by human monocyte-derived DCs (MDDCs) was analyzed by flow cytometry (FACS) and advanced imaging techniques. Viability, activation, function, and stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 55 publications
0
72
0
Order By: Relevance
“…15,49 Briefly, adenocarcinoma human alveolar basal epithelial cells (A549 cells) were grown under submerged conditions for 5 days on cell culture inserts (surface area of 4.2 cm 2 , pores with 3.0 μm diameter, high pore density PET membranes for six-well plates (BD Biosciences, Basel, Switzerland; 353502) at a density of 1 × 10 6 cells/mL). Monocytes were isolated from human buffy coat from healthy volunteers (Blood Donation Service, Bern University Hospital, Bern, Switzerland) by gradient centrifugation (Lymphoprep, Axis Scield, Oslo, Norway) as previously described by Blank et al 9 and Fytianos et al 13 Monocytes were differentiated into MDDCs by adding 10 ng/mL granulocyte−monocyte−colony stimulating factor and 10 ng/mL IL-4. MDMs were differentiated by adding 10 ng/mL monocyte−colony stimulating factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15,49 Briefly, adenocarcinoma human alveolar basal epithelial cells (A549 cells) were grown under submerged conditions for 5 days on cell culture inserts (surface area of 4.2 cm 2 , pores with 3.0 μm diameter, high pore density PET membranes for six-well plates (BD Biosciences, Basel, Switzerland; 353502) at a density of 1 × 10 6 cells/mL). Monocytes were isolated from human buffy coat from healthy volunteers (Blood Donation Service, Bern University Hospital, Bern, Switzerland) by gradient centrifugation (Lymphoprep, Axis Scield, Oslo, Norway) as previously described by Blank et al 9 and Fytianos et al 13 Monocytes were differentiated into MDDCs by adding 10 ng/mL granulocyte−monocyte−colony stimulating factor and 10 ng/mL IL-4. MDMs were differentiated by adding 10 ng/mL monocyte−colony stimulating factor.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that MHC-II expression was not impaired after PVA-COOH and PVA-NH 2 AuNP exposure in suspension experiments using MDDM monocultures. Blank et al 33 There is evidence in the literature for the utilization of DC-SIGN AuNPs in biomedical applications. Arnaiz et al 38 synthesized 1.8 nm gold glyconanoparticles, some of which were internalized by immature DCs by both DC-SIGN-and non-DC-SIGN-mediated pathways, while the other part was colocalized with DC-SIGN receptors.…”
mentioning
confidence: 99%
“…After AuNP exposure, MDDCs were fixed with 2.5% glutaraldehyde in HEPES buffer (Sigma Aldrich, St. Luis, MO, USA) and dehydrated, embedded and sectioned as described in Blank et al 1 TEM pictures were captured using a Hitachi H-1700 TEM (Hitachi, Japan) at a resolution of 4.78 nm/pixel (overviews) and 1.96 nm/pixel (details) and recorded on a SIS Morada CCD camera (Olympus, Japan).…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Inserts were placed in six-well culture plates (BD biosciences) and cells were grown for 5 days under submerged conditions (2 ml medium in the upper and 3 ml in the lower chamber of the insert). Peripheral human blood monocytes were isolated from human blood buffy coats (Blood Donation Service, Bern University Hospital, Bern, Switzerland), as previously described by Blank et al (2011). Monocytes were cultured for 6 days at a density of 10 6 cells/ml in supplemented RPMI medium as used for the epithelial cells.…”
Section: Lung Cell Culturesmentioning
confidence: 99%